Gene knockdown in malaria parasites via non-canonical RNAi - Hentzschel, Franziska; Müller, Ann-Kristin; Grimm, Dirk (Nucleic acids research, 2020)
Abstract. The lack of endogenous RNAi machinery in the malaria parasite Plasmodium hampers gene annotation and hence antimalarial drug and vaccine development.